Justice Climate and Peer Justice Climate: A Closer Look. (October 2013) - Li, Andrew; Cropanzano, Russell; Bagger, Jessica
We provide an empirical examination of peer justice climate, defined as team-level judgments of the fairness with which coworkers generally treat one another, and justice climate, defined as team-level judgments of the fairness with which the team is collectively treated by an authority figure. Based on previous theoretical work, we tested a hierarchical structural model determining that peer justice climate was best represented as three first-order factors, which combine into a single second-order dimension. We found a similar two-level structure for justice climate. We also found that the relationship between peer justice climate and team satisfaction was mediated by cooperative team process.